2016
DOI: 10.4103/0301-4738.195002
|View full text |Cite
|
Sign up to set email alerts
|

Association between the p53 codon 72 polymorphism and primary open-angle glaucoma risk: Meta-analysis based on 11 case–control studies

Abstract: The TP53 is important in functions of cell cycle control, apoptosis, and maintenance of DNA integrity. Studies on the association between p53 codon 72 polymorphism and primary open-angle glaucoma (POAG) risk have yielded conflicting results. Published literature from PubMed and Web of Science databases was retrieved. All studies evaluating the association between p53 codon 72 polymorphisms and POAG were included. Pooled odds ratio (OR) and 95% confidence interval (CI) were calculated. Eleven separate studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
0
15
0
2
Order By: Relevance
“…The Arg72Pro functional polymorphism of TP53 has been widely assessed in cancer susceptibility studies that have yielded contradictory results. In Iran, investigations on this SNP in primary open angle glaucoma (50) and breast (25) and colorectal (21) cancers have indicated associations with disease risk, but no evidence of association has been identified in gastric (51,52) and head and neck (53) cancer, oral squamous cell carcinoma (54) and also hepatitis C infection (55).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Arg72Pro functional polymorphism of TP53 has been widely assessed in cancer susceptibility studies that have yielded contradictory results. In Iran, investigations on this SNP in primary open angle glaucoma (50) and breast (25) and colorectal (21) cancers have indicated associations with disease risk, but no evidence of association has been identified in gastric (51,52) and head and neck (53) cancer, oral squamous cell carcinoma (54) and also hepatitis C infection (55).…”
Section: Discussionmentioning
confidence: 99%
“…In ulcerative colitis, a type of inflammatory bowel disease in which cytokines and inflammatory mediators including tumor necrosis factor-α and interleukin-6, and arachidonic acid metabolites including prostaglandin E2 and leukotriene B4 are involved (60), the presence of the proline homozygous genotype (Pro/Pro) significantly increased the disease duration (>7 years) and was more frequent in patients with continuous disease course (61). Previously, it has been indicated that the presence of the proline allele and its homozygous genotype is associated with the risk of ulcerative colitis (Pro allele: OR, 7.8; Pro/Pro: OR, 35.2) and primary open-angle glaucoma (Pro allele: OR, 2.1; Pro/Pro: OR, 3.9) in Iranian subjects (50,62). In the Kuwaiti population, CAD prevalence exhibited an association with type 2 diabetes and high levels of triglyceride and cholesterol; however, there was no evidence of any influence of TP53 codon 72 genotypes (31).…”
Section: Frequency N (%) -------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…Así, teniendo en cuenta la diferente capacidad apoptótica de ambas variantes, se ha estudiado la influencia del polimorfismo Arg72Pro ampliamente en cáncer y en enfermedades neurodegenerativas(Gomez-Sanchez et al 2011;Lanara et al 2013).En este sentido, se ha establecido una relación entre el SNP Arg72Pro de Tp53 y el pronóstico funcional en pacientes que han sufrido un ictus(Gomez- Sanchez et al 2011). El estudio muestra que el genotipo Arg/Arg se relaciona con un peor estado funcional tras ictus, tanto isquémico como hemorrágico(Gomez-Sanchez et al 2011).En glaucoma primario de ángulo abierto, primera causa de neurodegeneración óptica, se ha descrito la importancia del polimorfismo Arg72Pro en cuanto al riesgo, de manera que los pacientes con mayor riesgo son los que portan el alelo Pro(Neamatzadeh et al 2015).Se han publicado numerosos estudios en pacientes sobre la influencia del polimorfismo Arg72Pro en relación al riesgo(Lanara et al 2013), pronóstico (Cescon et al 2009) y respuesta al tratamiento (Tecza et al 2015) de una amplia variedad de tipos de cáncer. Así, se ha descrito que ser portador del alelo Pro 72 incrementa el riesgo y susceptibilidad en cáncer de pulmón (Qiao & Hu 2013) y mama (Gonçalves et al 2014), entre otros (Whibley et al 2009).…”
unclassified
“…la mitocondria(Dumont et al 2003;Gomez-Sanchez et al 2011). En este sentido, la mayor vulnerabilidad al ßA que describimos en la variante Arg se debe, al menos en parte, a su mayor capacidad para acumular p53 en la mitocondria, respecto de la variante Pro que se acumula fundamentalmente en el núcleo.Estos resultados refuerzan nuestra idea de que la alteración de la homeostasis mitocondrial por interferencia con p53 tras su estabilización, es la responsable de la neurodegeneración asociada al ßA.La diferente susceptibilidad de las neuronas a la apoptosis que confiere el SNP tiene relevancia en pacientes de distintas patologías, como son el ictus (Gomez-Sanchez et al 2011) y el glaucoma primario de ángulo abierto(Neamatzadeh et al 2015). Si bien nuestros resultados en neuronas in vitro parecen sugerir que el SNP Arg72Pro podría condicionar el riesgo y/o la progresión de la EA, los escasos estudios que hay en la literatura difieren en sus conclusiones.…”
unclassified